Increasing Education-Based Disparities in Healthy Life Expectancy Among U.S. Non-Hispanic Whites, 2000–2010. (11th November 2019) - Cantu, Phillip A; Sheehan, Connor M; Sasson, Isaac; Hayward, Mark D
Abstract: Objectives: To examine changes in Healthy Life Expectancy (HLE) against the backdrop of rising mortality among less-educated white Americans during the first decade of the twenty-first century. Methods: This study documented changes in HLE by education among U.S. non-Hispanic whites, using data from the U.S. Multiple Cause of Death public-use files, the Integrated Public Use Microdata Sample (IPUMS) of the 2000 Census and the 2010 American Community Survey, and the Health and Retirement Study (HRS). Changes in HLE were decomposed into contributions from: (i) change in age-specific mortality rates; and (ii) change in disability prevalence, measured via Activities of Daily Living (ADL) and Instrumental Activities of Daily Living (IADL). Results: Between 2000 and 2010, HLE significantly decreased for white men and women with less than 12 years of schooling. In contrast, HLE increased among college-educated white men and women. Declines or stagnation in HLE among less-educated whites reflected increases in disability prevalence over the study period, whereas improvements among the college educated reflected decreases in both age-specific mortality rates and disability prevalence at older ages. Discussion: Differences in HLE between education groups increased among non-Hispanic whites from 2000 to 2010. In fact, education-based differences in HLE were larger than differences in total life expectancy. Thus, the lives of less-educated whites were not only shorter, on average, compared with their college-educated counterparts, but they were also more burdened with disability.